2017
DOI: 10.1177/0022146517748412
|View full text |Cite
|
Sign up to set email alerts
|

On the Weak Mortality Returns of the Prison Boom: Comparing Infant Mortality and Homicide in the Incarceration Ledger

Abstract: The justifications for the dramatic expansion of the prison population in recent decades have focused on public safety. Prior research on the efficacy of incarceration offers support for such claims, suggesting that increased incarceration saves lives by reducing the prevalence of homicide. We challenge this view by arguing that the effects of mass incarceration include collateral infant mortality consequences that call into question the number of lives saved through increased imprisonment. Using an instrument… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 44 publications
1
9
1
Order By: Relevance
“…We heed recent calls to abandon reliance on statistical significance in interpreting research results, in favor of more detailed and nuanced presentation and of statistical analyses, with the recognition that p values and decisions about what research ideas should be explored further have no association [23]. Given the literature on neighborhood effects on PTB among African American women which identified few true confounders [19,24], and the literature on the community effects of mass incarceration [14], sociodemographic variables may lie on the pathway linking preconception neighborhood mass incarceration to PTB. Adjusting for potential mediators would compromise the precision of our estimates, and attenuate the associations we were trying to identify [25]; we therefore present unadjusted models.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We heed recent calls to abandon reliance on statistical significance in interpreting research results, in favor of more detailed and nuanced presentation and of statistical analyses, with the recognition that p values and decisions about what research ideas should be explored further have no association [23]. Given the literature on neighborhood effects on PTB among African American women which identified few true confounders [19,24], and the literature on the community effects of mass incarceration [14], sociodemographic variables may lie on the pathway linking preconception neighborhood mass incarceration to PTB. Adjusting for potential mediators would compromise the precision of our estimates, and attenuate the associations we were trying to identify [25]; we therefore present unadjusted models.…”
Section: Discussionmentioning
confidence: 99%
“…Two existing state-level analyses revealed positive associations between imprisonment and infant mortality rates [14,15]. One existing study using Pregnancy Risk Assessment Monitoring System data from 1990 to 2003 found that maternal and/or paternal incarceration was a significant predictor of infant mortality [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…crime reduction) against any unintended and hidden costs. On this point, recent work has suggested the one fruitful avenue is “to more fully assess the incarceration ledger and the potential offsetting consequences of the prison boom for health inequalities.” ( Light and Marshall, 2018 : p. 15). Our study highlights the degree to which prison booms may contribute to a weakening of health care infrastructure, which in turn may generate greater vulnerabilities for population health.…”
Section: Discussionmentioning
confidence: 99%
“…The final social variables in the model were percent Non-Hispanic Black population (state) [ 23 ], Black-White marriage rate (state) [ 21 , 29 ], a hypersegregation index (county) [ 22 24 , 30 32 ], Black incarceration rate (state) [ 7 , 13 , 33 ], and percent of voting age population casting votes (state) [ 11 ]. The Black-White marriage rate, calculated as the percentage of married Black individuals with a White spouse, was selected as a contextual measure of social integration [ 29 , 34 , 35 ].…”
Section: Methodsmentioning
confidence: 99%